MODEL MATEMATIKA ALIRAN KONVEKSI BEBAS FLUIDA VISKOELASTIK YANG MELEWATI SILINDER ELIPTIK DENGAN PENGARUH MAGNETOHYDRODYNAMICS (MHD) - Annisa Dwi Sulistyaningtyas (WAHANA, 2018)
In fluid case, the mathematical model is the basic for translating a problem into a mathematical language using an equation or function. The governing equation is developed from continuity equation, momentum equation, and energy equation. Fluid characteristics are viscous and elastic result in boundary layer on the surface of elliptic cylinder. Dimensional equations are transformed into non-dimensional form and then classified into the similarity equations using boundary layer theory with influence of magnetic force. The results of this research is mathematical model of free convection flow in viscoelastic fluid passing through the elliptic cylinder with magnetohydrodinamics (MHD). For variation of magnetohydrodinamics (MHD) parameter, velocity and temperature increase when the parameter increases.